TEKANAN DARAH SISTOLIK LEBIH TINGGI PADA SORE DARIPADA PAGI HARI PADA USIA 45-65 TAHUN - Wulandari, Anindra Novita; Samara, Diana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Blood pressure is the pressure of the blood pumped by the heart against the walls of the arteries and is divided into systolic and diastolic. Blood pressure decreases 10% in the evening at normal circadian rhythms and rises again in the morning. Insomnia is one of the factors that can affect blood pressure. This study aims to look at differences in morning and evening blood pressure at the age of 45–65 years. The research method uses observational analytic with a cross sectional approach. Collecting samples using consecutive non-probability sampling. Subjects aged 45–65 were 301 people. Blood pressure was measured in the morning and evening. Insomnia data obtained based on a questionnaire. The statistical test used paired t test with a significance of p <0.05. The results showed a significant difference between morning and evening systolic blood pressure (P = 0,023), but there was no difference between morning and evening diastolic blood pressure (P = 0,224). There is a relationship between insomnia and morning blood pressure (p=0,001). The conclusion from the research results is that systolic blood pressure in the afternoon is higher than in the morning. Morning blood pressure is associated with difficulty sleeping at night.